Mimebot: spherical robot visually imitating a rolling sphere. Issue 1 (3rd April 2017) - Tsuchida, Shuhei; Takemori, Tatsuya; Terada, Tsutomu; Tsukamoto, Masahiko
Abstract : Purpose: When designing a performance involving people and mobile robots, the required functions and shape of the robot must be considered. However, it can be difficult to account for all of the requirements. The purpose of this paper is to discuss a mobile robot in the shape of a ball that is used in theatrical performances. Design/methodology/approach: The paper proposes a mobile robot that can give the audience the optical illusion of the unique movements of a sphere by mounting a spherical light-emitting diode (LED) display on a high-agility wheeled robot. Findings: It was found that movements that are difficult to implement with existing mechanisms can nonetheless be visualized through the use of light. Originality/value: The paper proposes the concept of using pseudo-physical movements in performances with robots. The authors built a robot that visually reproduces the movements of a rolling sphere and is capable of faster movements and easier position estimations in comparison with previous spherical robots.